Construction and Phase I Clinical Evaluation of the Safety and Immunogenicity of a Candidate Enterotoxigenic Escherichia coli Vaccine Strain Expressing Colonization Factor Antigen CFA/I - Turner, Arthur K; Beavis, Juliet C; Stephens, Jonathan C; Greenwood, Judith; Gewert, Cornelia; Thomas, Nicola; Deary, Alison; Casula, Gabriella; Daley, Alexandra; Kelly, Paul; Randall, Roger; Darsley, Michael J (Infection and Immunity, 2006)
Oral delivery of toxin-negative derivatives of enterotoxigenic Escherichia coli (ETEC) that express colonization factor antigens (CFA) with deletions of the aroC, ompC, ompF, and toxin genes may be an effective approach to vaccination against ETEC-associated diarrhea. We describe the creation and characterization of an attenuated CFA/I-expressing ETEC vaccine candidate, ACAM2010, from a virulent isolate in which the heat-stable enterotoxin (ST) and CFA/I genes were closely linked and on the same virulence plasmid as the enteroaggregative E. coli heat-stable toxin (EAST1) gene. A new suicide vector (pJCB12) was constructed and used to delete the ST and EAST1 genes and to introduce defined deletion mutations into the aroC, ompC, and ompF chromosomal genes. A phase I trial, consisting of an open-label dose escalation phase in 18 adult outpatient volunteers followed by a placebo-controlled double-blind phase in an additional 31 volunteers, was conducted. The vaccine was administered in two formulations, fresh culture and frozen suspension. These were both well tolerated, with no evidence of significant adverse events related to vaccination. Immunoglobulin A (IgA) and IgG antibody-secreting cells specific for CFA/I were assayed by ELISPOT. Positive responses (greater than twofold increase) were seen in 27 of 37 (73%) subjects who received the highest dose level of vaccine (nominally 5 x 10⁹ CFU). Twenty-nine of these volunteers were secreting culturable vaccine organisms at day 3 following vaccination; five were still positive on day 7, with a single isolation on day 13. This live attenuated bacterial vaccine is safe and immunogenic in healthy adult volunteers.